(untitled) (Research, Society and Development, 2021)
In Brazil there is no national database that includes the profile of burn patients, therefore, the aim of this study was to describe the epidemiological, clinical and hospitalization characteristics of children admitted to a reference center for the treatment of burns ( CTQ) of Espírito Santo. A cross-sectional descriptive epidemiological study was carried out based on data from electronic and physical medical records of children admitted to the CTQ from August 2019 to July 2020. Within the sample studied, most are under five years old of age, are male and have heat as the main etiological cause (93.1%). On average, 14% (SD 11) of body surface was burned. The most affected body regions were: trunk (64.7%), upper limbs (55.9%) and head and neck (44.1%). The depth of most burns was second degree (86.3%) and severity classified as medium burn (48%). Patients remained in the hospital for an average of 23 days (SD=27, minimum 3 and maximum 115 days), and 91.2% underwent at least one wound debridement procedure. The results of this study, added to the specific knowledge of a region (Espírito Santo), can help in the development of strategies to raise awareness about burns and provide guidance to parents and the general public, through educational programs and prevention campaigns.